Visitor’s adaptability toward natural elements and regulations in Penang National Park, Malaysia - Rahmi, Novalia; Mohamed, Noorizan; Mariapan, Manohar; Saidon, Mohd. Nazri (Universiti Putra Malaysia Press, 2010)
In 2006, Penang National Park (PNP) became the second National Park destination in Malaysia. Through PNP complaint forms, the visitor reports some discomfort conditions from other visitors, facilities, and services while in the park. Cleanliness, signage, operational time of certain facilities and guide behaviour were negatively reported by visitors. Thus, the negative conditions will have an adverse effect on PNP as a conservation area. With this in mind, the research was carried out to learn about visitor’s adaptation in PNP. A total of 402 questionnaires were administered to domestic and international visitors. Some of the items in the questionnaire were further grouped into 4 concepts. Results show significant differences between the mean scores for domestic and international visitors on the concepts of regulation, active-activity, passive-activity and noisy condition, whereby the international visitors were found to be more likely to adapt to the conditions than those of the domestic. On the concept of regulation, both the international and domestic visitors could adapt toward the Park’s regulation. The significance of the results will be forwarded to the PNP management for their consideration of the visitors’ level of adaptation to reduce the negative impacts in the effort keep environmental sustainability in PNP.